MENGINTEGRASIKAN PSIKOLOGI: PELUANG ATAU MIMPI? - T. Dicky Hastjarjo (Buletin Psikologi, 2008)
“How can institutional psychology be taken seriously when psychologists themselves disagree over fundamental issues such as how to define or investigate the discipline’s core subject matter” (Yanchar, 2000, h. 248).